PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA UD SINAR GEMILANG NGANJUK - Novitasari, Violita Dewi; Widodo, Eko; Muttaqien, Zaenul; Handayani, Rani (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This research aims to determine the influence of leadership styles and compensation for employees ' performance in UD Sinar Gemilang. This research data is derived from the method of presenting data from the response of respondents (questionnaires), as well as the results of other research that is relevant with the objects studied, in this case the primary data of UD Sinar Gemilang. The sample in the study was 35 respondents. The sample withdrawal method uses a saturated sampling where sampling is used throughout the population. The analyses used in this study were multiple linear regression analyses using SPSS 16 programs. The results of this research show that the style of leadership has no effect and is not significant to the employee's performance, compensation has a positive and significant impact on employee performance. While the simultaneous leadership and compensation styles have a positive and significant effect on the performance of UD Sinar Gemilang Nganjuk employees.